The effectiveness and safety of fixed low‐dose prothrombin complex concentrates in patients requiring urgent reversal of warfarin (CME). Issue 7 (15th October 2012) - Varga, Cindy; Al‐Touri, Sultan; Papadoukakis, Stella; Caplan, Stephen; Kahn, Susan; Blostein, Mark
<x xml:space="preserve">Abstract</x> Background A rapid method of reversal is required for patients on warfarin who suffer acute bleeding or require emergency surgery. Prothrombin complex concentrates (PCCs) have recently been recommended by the Canadian Blood Services for use at a fixed low dose of 1000 IU of Factor (F)IX activity. The main goal of this study was to investigate both the effectiveness and the safety of fixed low‐dose PCCs. Study Design and Methods We retrospectively reviewed charts from 103 patients who received PCCs for reversal of warfarin therapy. Results A total of 103 patients were treated with PCC at a single fixed dose of 1000 IU of F IX activity. Fifty patients (48.5%) had a final international normalized ratio (INR) response of not more than 1.5 and an additional 45 patients (43.7%) had a final INR response between 1.6 and 2.0. However, 86 patients (83.5%) had an excellent clinical response consisting of control of bleeding without the requirement of additional measures. In a multivariable model, patients who received fresh‐frozen plasma and patients who were given doses greater than 1000 IU of PCC were both identified as predictors of a poor clinical response (odds ratio [OR] 3.48, 95% confidence interval [CI] 0.76‐15.89, p = 0.11; and OR 10.8, 95% CI 2.08‐56.28, 95% CI, p = 0.005, respectively). There were five adverse events up to 30 days after PCC use. Conclusion At a fixed dose of 1000 IU of F IX activity, PCC seems to be effective and safe but randomized controlled trials, specifically examining different doses of PCC, are required to confirm the above observations.